THE EFFECT OF FORMALDEHYDE EXPOSURE AND YOGURT SUPPLEMENTATION ON PROFILE AND CHARACTER OF HEPAR TISSUE PROTEIN OF RATS (Rattus norvegicus) - Chanif Mahdi; Aulaniam Aulaniam (Indonesian Journal of Chemistry, 2010)
Formaldehyde is a simplest organic compound of aldehyde or alkanal group. Formaldehyde is a toxic and carcinogenic substance. Formaldehyde contamination through food or feeding diet continuously is very dangerous for the body, especially for bodies organ for instances likes hepar and kidney. Because formaldehyde is sources of reactive oxygen species (ROS) and free radicals substances for the body. This purpose of the study is to know the effect of formaldehyde exposure and yogurt supplementation on profile and characters of rats (Rattus norvegicus) protein hepar tissues. The research methods is laboratory methods. The protein profiles determined by electrophoresis (SDS-PAGE) methods. The character of hepar protein tissue determined by ELISA, Dot Blot and Western Blot methods. The result showed that formaldehyde exposure through the feeding diet of rats affect on profile of hepar protein tissue, that characterized by appear of new band of specific protein with molecule weigh is 29.6 kDa (PSForm 29.6). Yogurt supplementation on rat that exposure by formaldehyde through the feeding diet of rat, that characterized by expressing of new band of specific protein with relative molecule weight 24.8 kDa (PSYogh 24.8 kDa), and followed by depressed or dispear of protein specific band of 29.6 kDa(PSForm 29.6 kDa). The result showed that isolated protein PSForm 29.6 kDa have a antigenecity character.